Secure tenure or equal access? Farmers’ preferences for reallocating the property rights of collective farmland and forestland in Southeast China - Yiwen, Zhang; Kant, Shashi (Land use policy, 2022)
Understanding farmers’ preferences for efficiency and equity regarding different land use rights is necessary for the success of land reforms because economic efficiency with equity is the key distinguishing feature of China’s land reforms. This paper presents a comparative analysis of farmers’ preferences for tenure security (a measure of efficiency) and distribution equality in two similar but distinct land use practices: reallocating physical farmland and reallocating forest monetary shares, both of which contradict government-imposed tenure individualization policies but have long co-existed in some parts of Southeast China. The analysis includes farmers’ self-interested as well as prosocial motivations. Data from 222 households, collected from five communities using surveys and a public good game, shows that farmers have a high preference for distribution equality over tenure security in both types of land reallocations. Using bivariate probit models, we find farmers’ preferences for reallocating land property rights are associated with their prosocial preferences, but the influence of prosocial preferences varies across reallocations. Moreover, the higher cost of implementing farmland reallocations contributes to farmers’ higher preference for tenure security in farmland reallocations than in forest shareholdings reallocations. The research provides empirical evidence of the influence of prosocial motivations on farmers’ land property rights preferences and demonstrates that farmers in the same communities may have different preferences for land property rights for two land uses (agriculture and forestry), and the influencing factors and their influence on land property rights preferences may also vary across land uses. •China’s land rights reallocations show the equal access vs. secure tenure trade-off.•Farmers’ preferences for reallocations manifest their prosocial motivations.•Reallocations take different forms across various land use contexts.•Reallocating physical farmland is more costly than reallocating forest shareholdings.•Cost factors affect how farmers balance equal access against secure tenure.